Legal Protection for Companies Experiencing Boycott Practices from the Perspective of Economic Law Enforcement - Siska Fitria Bodamer; Beby Sendy; Bambang Fitrianto (Fakultas Hukum Dehasen, 2026)
This study aims to analyze legal protection for companies experiencing boycott practices from the perspective of Indonesian economic law enforcement, particularly through Law No. 5 of 1999 on the Prohibition of Monopolistic Practices and Unfair Business Competition. The research employs a normative juridical method with a literature-based approach, utilizing statutory regulations, books, official documents, publications, and prior research findings as supporting materials. The results indicate that the mechanisms of the Business Competition Supervisory Commission (KPPU) are effective in protecting affected parties through investigations and binding decisions. However, challenges remain, including legal uncertainty arising from MUI Fatwa No. 83 of 2023 and the spillover effects of losses along supply chains, which necessitate normative synchronization. The conclusion emphasizes the need to balance consumer rights and economic efficiency, and recommends the establishment of boycott verification guidelines and the strengthening of enforcement mechanisms to ensure business certainty.